2010
DOI: 10.1002/mrm.22630
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of perfusion and arterial transit time in myocardium using free‐breathing myocardial arterial spin labeling with navigator‐echo

Abstract: Arterial spin labeling (ASL) provides noninvasive measurement of tissue blood flow, but sensitivity to motion has limited its application to imaging of myocardial blood flow. Although different cardiac phases can be synchronized using electrocardiography triggering, breath holding is generally required to minimize effects of respiratory motion during ASL scanning, which may be challenging in clinical populations. Here a freebreathing myocardial ASL technique with the potential for reliable clinical application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 27 publications
(35 reference statements)
6
65
0
Order By: Relevance
“…Our 4D Time-SLIP technique differs from the FAIR technique in the following aspects: 1) After the non-selective pulse, we switch the selective pulse on to tag the aortic root and switch it off to serve as control, while FAIR uses a non-selective pulse to tag the whole heart and a selective pulse in the imaging as a control (Zun et al, 2009a); 2) 4D Time-SLIP uses 3D data acquisition with multiple tagging delays, and FAIR uses single slice (Zun et al, 2009a(Zun et al, , 2011Wang et al, 2010) or multiple slice 2D acquisition in general (Cambell-Washburn et al, 2013a,b);…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our 4D Time-SLIP technique differs from the FAIR technique in the following aspects: 1) After the non-selective pulse, we switch the selective pulse on to tag the aortic root and switch it off to serve as control, while FAIR uses a non-selective pulse to tag the whole heart and a selective pulse in the imaging as a control (Zun et al, 2009a); 2) 4D Time-SLIP uses 3D data acquisition with multiple tagging delays, and FAIR uses single slice (Zun et al, 2009a(Zun et al, , 2011Wang et al, 2010) or multiple slice 2D acquisition in general (Cambell-Washburn et al, 2013a,b);…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, a non-contrast arterial spin labeling (ASL) technique, originally developed to study brain perfusion (Buxton et al, 1998;Petrella and Provenzale, 2000;Kim, 1995), has been applied to study myocardium perfusion (Zun et al, 2009a(Zun et al, ,b, 2011Wang et al, 2010;Epstein and Meyer, 2011). There are two methods of tagging blood in cardiac ASL.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize residual motion (particularly in navigatorgated scans), a non-rigid body motion correction was applied by maximizing the cross-correlation between image frames using symmetric diffeomorphic image registration by the ANTs software [20,21]. Afterwards, all images were brought in Osirix for image quality assessment, parameter quantification and region-of-interest (ROI) analyses.…”
Section: Image Post-processingmentioning
confidence: 99%
“…There has been preliminary work on myocardial ASL in humans (5)(6)(7)(8)(9). These preliminary studies have demonstrated the existence of an ASL signal in the heart, and while some have demonstrated signal increases with pharmacological stress, none has reported sufficient image quality and measurement consistency to provide useful diagnostic information in individual patients.…”
mentioning
confidence: 99%